2021
DOI: 10.3390/pr9030552
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Characteristics of Size-Segregated Particulate Water-Soluble Inorganic Ions and Potentially Toxic Metals during Wintertime in a High Population Residential Area in Beijing, China

Abstract: Airborne particulate matter (PM) pollution often occurs in the wintertime in northern China, posing a potential threat to human health. To date, there are limited studies about the metals and inorganic ions to link source apportionments and health risk assessments in the different size-segregated PM samples. In this study, our samples were collected by a high-volume air sampler from 26 December 2018 to 11 January 2019 in a high population residential area (Beijing). Water-soluble inorganic ions, metal elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…The EF was calculated using the following equation (K. Xiao et al, 2021) (1): EF = (C soli /V soil ) / (C lithosphere /V lithosphere ) (1) where C and V were denoted the concentrations of heavy metals in soils and in the lithosphere (the outer layer of the earth's crust) (mg/kg), respectively. There is no generally recognized grade for EF.…”
Section: Enrichment Factor (Ef)mentioning
confidence: 99%
See 1 more Smart Citation
“…The EF was calculated using the following equation (K. Xiao et al, 2021) (1): EF = (C soli /V soil ) / (C lithosphere /V lithosphere ) (1) where C and V were denoted the concentrations of heavy metals in soils and in the lithosphere (the outer layer of the earth's crust) (mg/kg), respectively. There is no generally recognized grade for EF.…”
Section: Enrichment Factor (Ef)mentioning
confidence: 99%
“…There is no generally recognized grade for EF. The EF values < 1.0 indicate a possible mobilization or depletion of trace elements, while EF values > 1.0 indicate that the heavy metal has been in uenced by anthropogenic activities (Xiao et al, 2021) (Taati et al, 2020).…”
Section: Enrichment Factor (Ef)mentioning
confidence: 99%
“…To determine the risk to human health, the probability of noncarcinogenic risk was evaluated by the hazard quotient (HQ), and the carcinogenic risk (CR) was examined (Xiao et al, 2021). Fine particles can travel deep into the lower lung area and are primarily deposited in bronchioles and alveoli, so they are difficult to eliminate because the alveolar area does not have protective mucus layers; in the inhalation route, fine particles play an essential role in endangering human health (Reid et al, 2016).…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…According to US-EPA risk 431 management guidelines, CR is the likelihood that an individual will develop any cancer after being 432 exposed to a cancer risk during their lifetime, and the acceptable risk range for CR is between 1 × 433 10 -6 and 1 × 10 -4 (Sun et al, 2014). The hazard index (HI) is the sum of the HQs applied to examine 434 the overall potential for noncarcinogenic impacts caused by chemicals (Xiao et al, 2021). If HI or 435 HQ is higher than one, there are noncarcinogenic risks, and the probability increases as the value 436 of HI or HQ increases (US-EPA, 1989).…”
Section: Accepted Manuscript 30mentioning
confidence: 99%
“…However, a study concluded that further controls on traffic emissions will have limited benefit in reducing the concentration of fine particles, except in countries where the use of diesel particle filters is not mandatory (e.g., outside the EU) [8,16]. Indeed, where policies and strategies are not implemented, air quality continues to worsen due to the increasing number of vehicles and power plants [17,18].…”
Section: Introductionmentioning
confidence: 99%